Strategies for Customer Acquisition and Retention: A Marketing Internship Experience at Shine Projects - Parimal, Sagar (ATLAS SkillTech University, 2025)
The global education industry is massive and vibrant with a market worth about six trillion dollars by 2024. It includes different parts like K-12, higher education, vocational training, and edtech. Its development has been steady thanks to increased enrolment rates, growing demand for lifelong learning and technological advancement.
Project Report on Strategies for Customer Acquisition and Retention: A Marketing Internship Experience at Shine Projects (2023-2025) Under the Guidance of Prof. Zuleika Homavazir
Keywords: global education; market worth; vocational training; technological advancement